Subtraction of Epstein–Barr virus and microsatellite instability genotypes from the Lauren histotypes: Combined molecular and histologic subtyping with clinicopathological and prognostic significance validated in a cohort of 1, 248 cases. Issue 12 (1st March 2019) - Huang, Shih‐Chiang; Ng, Kwai‐Fong; Yeh, Ta‐Sen; Cheng, Chi‐Tung; Lin, Jie‐Sian; Liu, Yu‐Jen; Chuang, Huei‐Chieh; Chen, Tse‐Ching
Abstract : Limited studies investigated clinicopathological and prognostic significance of histologic and molecular subgroups of gastric cancer concurrently. We retrospectively enrolled 1, 248 patients with gastric cancer who received radical gastrectomy with lymphadenectomy and classified these cases into the Epstein–Barr virus (EBV)‐associated and microsatellite instability (MSI)‐associated subtypes by EBV‐encoded small RNA in situ hybridization and immunohistochemical stains for DNA mismatch repair proteins, respectively. The remaining cases were categorized as the Lauren intestinal and diffuse/mixed subtypes. The clinicopathological and prognostic significance of the subtypes was examined by statistical analysis. In total, 65 (5.2%), 116 (9.3%), 496 (39.7%), 431 (34.5%) and 140 (11.2%) cases were identified as EBV‐associated, MSI‐associated, intestinal, diffuse and mixed subtypes, respectively. The EBV‐associated, MSI‐associated, intestinal and diffuse/mixed subtypes exhibited distinctive clinicopathological characteristics, including differences in age, gender, stump cancer, gastric location, tumor size, TNM stage, margin involvement, lymphatic/perineural invasion, HER2 status and recurrence pattern. The log‐rank test showed survival discrimination ( p < 0.001), and the multivariate analysis identified EBV‐associated and MSI‐associated cases demonstrated better outcomes than the diffuse/mixed subtype (EBV, HR 0.464, 95% CI 0.296–0.727, p = 0.001; MSI, HR 0.590, 95% CI 0.407–0.856, p = 0.005). EBV‐associated lymphoepithelioma‐like carcinoma cases had the most favorable outcome (HR 0.138, 95% CI 0.033–0.565, p = 0.006). In different clinical groups, the subtypes exhibited survival discrepancies. The EBV‐associated and diffuse/mixed cases exhibited more favorable response to chemotherapy. In conclusion, this combined classification, in parallel with the molecular subtypes specified in the Cancer Genome Atlas study, has implications for the clinical management of gastric cancer. Abstract : What's new? Gastric cancer is a heterogeneous disease from histologic and molecular viewpoints. Stratifying gastric cancer into Epstein–Barr virus‐positive, microsatellite instability‐associated and Lauren intestinal and diffuse/mixed subtypes demonstrates significant clinicopathological and prognostic discrimination, which is relevant to current genetic knowledge and clinical management. This combined molecular and histologic classification, correspondent to the molecular subtyping specified in the Cancer Genome Atlas study, is practically implementable with etiologic insight and therapeutic implications.